Characteristics and Treatment of Pneumonia Patients at Cut Meutia General Hospital North Aceh in 2022 - Muhammad Kautsar; Cut Khairunnisa (Proceedings of Malikussaleh International Conference on Health and Disaster Medicine (MICOHEDMED), 2024)
Pneumonia, an acute respiratory infection affecting the lungs, manifests as inflammation of lung parenchyma and can be caused by various infectious agents such as bacteria, fungi, viruses, and chemical substances. Pneumonia is a global health issue due to its high mortality rates, not only in developing countries but also in developed nations. There are 450 million recorded cases of pneumonia each year, resulting in approximately 4 million deaths. Length of stay for pneumonia patient is crucial as it correlates with the severity of the patient's condition and the associated costs or patient insurance. The general objective of this research is to determine the characteristics and treatment of the patient with the length of stay of pneumonia patients’ hospitalization at Cut Meutia General Hospital in North Aceh in 2022. This study employs a descriptive approach with a cross-sectional method, by collecting medical record data from 107 samples aged >18 years through total sampling. The research findings indicate that the majority of hospitalized pneumonia patients are aged > 60 years, categorized as elderly, male, with comorbidities, receiving non-ICU treatment. Mostly undergoing monotherapy antibiotics, and the majority of patients are discharged with improvement, with length of stay for < 7 days.